Pengaruh Pengetahuan,label halal,sikap,Religiusitas dan Harga terhadap Minat Beli pada Kosmetik Halal Import Korea - Fauziah Ramadhany, Suci (Airlangga Journal of Innovation Management, 2024)
This research aims to explore the effects of product knowledge, halal label, attitude, religiosity, and price on cosmetic purchasing decisions, by considering each variable in depth. The population of this study consists of Generation Z in Bogor. Using a quantitative approach, data was collected through questionnaires and analyzed using the SEM PLS application. The research results show that there is a positive and significant influence of product knowledge, halal label, religiosity, attitude, and price on purchasing decisions. Research shows that aspects such as product knowledge, halal labels, religiosity, attitude, and price have an important impact on consumer purchasing decisions. The implications of this research are very relevant for cosmetics industry owners and practitioners. Adequate information about products, belief in halal, religious values, positive attitudes towards brands, and price considerations all influence consumer purchasing choices. Therefore, companies must pay attention to these factors in their marketing strategies to increase product appeal and influence consumer purchasing behavior. A thorough understanding of consumer preferences is the key to achieving success in a competitive market environment.